Use of Real-world Evidence to Evaluate the Effectiveness of Herpes Zoster Vaccine. (22nd September 2018) - Tseng, Hung Fu; Sy, Lina S
Abstract: This article reviews the use of real-world evidence (RWE) from observational studies to evaluate herpes zoster vaccine effectiveness and complement clinical trial data that have known limitations. The use of RWE with appropriate study designs and cautious interpretation can be informative in decision-making. Understanding the advantages and limitations of studies yielding RWE can facilitate the critical evaluation of findings from different studies. This is a timely issue, as regulatory agencies are considering how RWE can contribute to the assessment of effectiveness in regulatory decision-making.